2013
DOI: 10.1302/0301-620x.95b4.30442
|View full text |Cite
|
Sign up to set email alerts
|

Scapular notching and osteophyte formation after reverse shoulder replacement

Abstract: This study provides recommendations on the position of the implant in reverse shoulder replacement in order to minimise scapular notching and osteophyte formation. Radiographs from 151 patients who underwent primary reverse shoulder replacement with a single prosthesis were analysed at a mean follow-up of 28.3 months (24 to 44) for notching, osteophytes, the position of the glenoid baseplate, the overhang of the glenosphere, and the prosthesis scapular neck angle (PSNA). A total of 20 patients (13.2%) had a no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(12 citation statements)
references
References 19 publications
1
10
1
Order By: Relevance
“…The rate we found (20.5 %) was low in comparison to rates reported for similar prostheses (e.g. Delta III) over similar follow-up times (56–96 % [ 17 , 19 ]) and for other prostheses that also have a medialized center of rotation (weighted mean of 63 % over 46-month mean follow-up) [ 20 ]. It should be noted that the rate we are reporting is still high in comparison to prostheses with a more lateralized center of rotation [ 21 , 22 ].…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…The rate we found (20.5 %) was low in comparison to rates reported for similar prostheses (e.g. Delta III) over similar follow-up times (56–96 % [ 17 , 19 ]) and for other prostheses that also have a medialized center of rotation (weighted mean of 63 % over 46-month mean follow-up) [ 20 ]. It should be noted that the rate we are reporting is still high in comparison to prostheses with a more lateralized center of rotation [ 21 , 22 ].…”
Section: Discussioncontrasting
confidence: 79%
“…Nyffeler et al [ 11 ] showed that placing the glenosphere beyond the inferior glenoid rim significantly improved adduction and abduction angles. Roche et al [ 20 ] showed that female patients without notching (though not male patients) showed significantly more glenosphere overhang than patients with notching. Other studies have shown no correlation between scapular notching and glenosphere positioning [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Inferior glenosphere overhang was measured on AP radiographs as the direct distance between the inferior margin of the glenosphere and inferior glenoid neck. [25] Glenosphere version was measured on the axial radiographs as the angle formed by a line connecting the most anterior medial and posterior medial aspects of the glenosphere and a line connecting the midpoint of the glenoid with the most medial part of the scapular spine. [26] Glenosphere-scapular neck angle was decided by 2 lines (a line connecting the most proximal medial and distal medial aspects of the glenosphere and a line along the inferior lateral bone of the glenoid rim) on the AP radiographs.…”
Section: Methodsmentioning
confidence: 99%
“…[26] Glenosphere-scapular neck angle was decided by 2 lines (a line connecting the most proximal medial and distal medial aspects of the glenosphere and a line along the inferior lateral bone of the glenoid rim) on the AP radiographs. [25] Moreover, the acromion-deltoid tuberosity distance was described as the length between the acromion and the deltoid tuberosity of the humerus with the arm in neutral rotation and 0° abduction as described by a previous study [27]. (Fig 1)…”
Section: Methodsmentioning
confidence: 99%
“…Gutiérrez and colleagues 13 also found that decreasing the neck shaft angle to create a more varus proximal humerus was the most important factor in increasing the impingement-free adduction. Roche and colleagues 14 reviewed the radiographs of 151 patients who underwent primary reverse TSA at a mean follow-up of 28.3 months postoperatively; they found that 13.2% of their patients had a notch and that, on average, their patients who had no scapular notch had significantly more inferior glenosphere overhang than those who had a scapular notch. Poon and colleagues 15 found that a glenosphere overhang of >3.5 mm prevented notching in their randomized control trial comparing concentrically and eccentrically placed glenospheres.…”
Section: Glenosphere Placementmentioning
confidence: 99%